Mosaic a print publication : a publication for young adults that divulges one’s social identity - Desy Indrawaty (2010)
A Final Year Project submitted in partial fulfilment of the requirements for the degree of Bachelor of Communication Studies with Honours 2009/2010. A publication that serves as a guide to life for undergraduates, graduates and young working professionals and raises the awareness of discovering one's social identity through cultural, social and lifestyle platforms.